Multicenter Evaluation with Eckardt Score of Laparoscopic Management with Heller Myotomy and Dor Fundoplication for Esophageal Achalasia in a Pediatric Population in Colombia (2021)
Background: Esophageal achalasia is a rare, chronic, and progressive neurodegenerative motility disorder that is characterized by a lack of relaxation of the lower esophageal sphincter. Laparoscopic Heller myotomy (LHM) is the ideal in our population. Multiple surgical and medical treatments have been raised. However, there has been a need to expand studies and generate a clear algorithm for an ideal therapeutic algorithm. Methods: Clinical record was retrospectively analyzed of patients who underwent LHM and Dor fundoplication evaluated with Eckardt score, at four Colombian medical centers between February 2008 and December 2018. Results: There were a total of 21 patients (12 males and 9 females, ages 8 months to 16 years). The time from onset of symptoms to surgery was between 5 months and 14 years. One patient had esophageal mucosa perforation, 2 patients were converted to open surgery, and 1 patient had a postoperative fistula. All patients were discharged 3 to 9 days postoperatively, at which time they tolerated normal oral feeding. During follow-up, all the patients had an improvement in nutritional status and a greater functional recovery; 4 had reflux and 1 had reflux-like symptoms. Conclusion: LHM with Dor-type fundoplication maintains the effectiveness of open surgery with low postoperative morbidity and mortality and good functional results according to Eckardt score evaluation. © Copyright 2021, Mary Ann Liebert, Inc., publishers 2021.